Cost-Of-Illness and its Determinants for Type 2 Diabetes Mellitus in Bangladesh: Protocol for a Cross-Sectional Study - Afroz, Afsana; Alam, Khurshid; Alramadan, Mohammed J; Hossain, Md Nassif; Chowdhury, Hasina Akhter; Ali, Liaquat; Magliano, Dianna J; Billah, Baki (Bangladesh Journal of Medical Science, 2019)
Background: Diabetes is one of the most prevalent non-communicable diseases (NCDs) all over the world and leading cause of death, disability, and economic loss. Diabetes imposes a heavy economic burden on individuals, their families and society as a whole. The aim of this study is to estimate the economic burden of type 2 diabetes mellitus (T2DM) in Bangladesh and to find association between glycemic control and Health Related Quality of Life with cost-of-illness (COI). Methodology: This will be an analytical cross-sectional cost-of-illness study. Within a specific time period participants aged ≥18 years, registered with Bangladesh Diabetic Somiti and having type 2 diabetes for more than one year will be recruited from selected hospitals inside and outside Dhaka to cover all level of health care services. A pre-tested electronic questionnaire will be used for data collection. The questionnaire will include demographic, clinical, behavioral information of the participants and all cost related information related to diabetes management during last one year. Descriptive statistics will include mean (±SD) or median (percentile) or relative frequencies (percentage) depending on the data. Two samples independent t-test or Mann-Whitney U-test, ANOVA or Kruskal-Wallis test and chi-squared tests will be used for univariate analysis. The multivariable regression analysis and bootstrap method will also be employed to analyze the relationship between the total cost of care (dependent variable) and several potential explanatory variables (independent variables). Logistic regression analysis will be performed to assess the factors affecting glycemic control and health related quality of life (HRQoL). The calculated total cost-of-illness will be projected for T2DM in Bangladesh by a mathematical modelling. Discussion: The results of the study will be useful as background information to forecast the economic burden of type 2 diabetes mellitus in Bangladesh and will be beneficial to conceptualize health strategies at national level. Furthermore, recognizing the factors of cost-of-illness will help both patients and health care providers to improve the management plan and cost control and hence, to have better quality of life. Evidence about the magnitude of the burden of T2DM is important for public health policymakers who are involved in making health care priorities and allocating scarce resources to facilitate the greatest benefits for type 2 diabetic people in Bangladesh. Bangladesh Journal of Medical Science Vol.18(3) 2019 p.501-507